Analysis of sub-synchronous oscillation characteristics of PMSGs based on transient energy - Yan, Gangui; Wang, Yupeng; Yang, Cheng; Yue, Lin (Frontiers in Energy Research, 2023)
Faced with the problem of sub-synchronous oscillation (SSO) caused by the interaction between permanent magnetic synchronous generator (PMSG)-based wind farms and weak AC grids, we construct a transient energy function model that follows the structure of a PMSG. The transient energy composition of a PMSG is analyzed, and the dissipation energy expression that can intuitively reflect the development trend of SSO is derived, reflecting the damping level of a grid-connected wind power system. Furthermore, in response to the problem of mutual coupling between the control links of the PMSG during the SSO process, which hinders oscillation characteristic assessment, a method based on oscillation energy is proposed to analyze the oscillation characteristics. Considering the dynamic changes in the output of the phase-locked loop during sub-synchronous oscillation, the transient energy dominated by various control links is derived, and the effects of the phase-locked loop, current inner loop, and voltage outer loop on transient energy and oscillation characteristics are analyzed. The simulation verifies the effectiveness of the analysis of the transient energy model.